Розвиток та інтерпретація квантових уявлень в Україні - Щербак, О.А. (Питання історії науки і техніки, 2009)
Развитие квантовых представлений и принятие их научным обществом Украины
можно проиллюстрировать на примере формирования теории аномального эффекта
Зеемана в рамках строй квантовой механики. В данной статье проведен сравнительный анализ теорий Лоренца, Фогта, Роба, Зоммерфельда, Ритца, и Кордыша, показана эволюция основных понятий в историко-физическом контексте. Только так можно
показать эволюцию основных идей, и переход к современной неклассической физике. In the given paper the comparative data analysis of Lorentz theory, theory of Voight, theory
of Robb, theory of Sommerfeld, theory of Ritz, theory of Kordisch; theories has been conducted,
the evolution of the attitude to the main concepts in historical and physical context has
been exposed. Earlier unknown Kordisch’s materials have been analyzed for the first time.
Only this way the evolution of the attitude to the main ideas, and transition to modern nonclassical
physics can be shown.